(untitled) (Research, Society and Development, 2018)
Adolescence is a period of rapid biological and psychosocial changes and schools seem to be an appropriate place to develop interventions to promote mental health. The objective of the present study was to do an integrative review to identify the main themes in terms of mental health in the adolescence and to analyze the main strategies of intervention adopted and their results. Of 285 articles found, only 5 were selected as they were interventions on mental health promotion with adolescents in schools. We observed a focus on developing social competences, which brought apparent positive results in terms of creating a wellness environment and promoting better life quality for adolescents.